Palladium-catalysed addition of aryl halides to N-sulfinylamines for the synthesis of sulfinamides - Wei, M-K; Moseley, D; Bär, R; Sempere, Y; Willis, M (American Chemical Society, 2024)
Sulfinamides are versatile, synthetically useful intermediates and final motifs. Traditional methods to synthesise sulfinamides generally require substrates with pre-installed sulfur centers. However, these precursors have limited commercial availability, and the associated synthetic routes often require harsh reaction conditions and highly reactive reagents, thus severely limiting their application. Herein, we report the synthesis of sulfinamides from aryl and alkenyl (pseudo) halides and N-sulfinylamines, enabled by palladium catalysis. The reactions use mild conditions and are achieved without the use of highly reactive pre-formed organometallic reagents, resulting in transformations of broad generality and high functional group tolerance. In particular, substrates featuring protic and electrophilic functional groups can be used successfully. Modification of complex aryl cores and natural product derivatives demonstrate the utility of this method.